Wisata Religi di Pura Uluwatu - Kusumaningrusm, Anisa Putri; Awaloedin, Dipateruna; Pradini, Gagih; Ardani, Putri Aulia; Sanjaya, Surya (Peneliti.net, 2023)
This study aimed to the history of the village of Pecatu Uluwatu Temple development of Pura Uluwatu, Bali as a tourism destination, and contribution to the study of history Pura Uluwatu. This study used a qualitative approach, namely: study design, determining the location of research techniquesdetermination techniques, data collection techniques (observation, interviews, document studies), the validity of the data (triangulation triangulation of data or data sources and triangulation methods), and data analysis techniques. These results indicate that there are two sources of Pura Uluwatu on the written sources and oral sources. Uluwatu development as a tourist attraction in Bali, Pura Uluwatu Contribution existence for history education, among others: Pura Uluwatu save mandate contained in the story of the history of the existence of Uluwatu Temple itself, Cultivating a love of students or learners to legacy historical / cultural heritage into Bali, Raise awareness of historical and cultural insights on students to participate in maintaining and preserving archaeological heritage / history that is around us, A visit to Uluwatu Temple can help to gain understanding more explicit about the learning materials in schools relating to local history materials.